La scienza tra consenso e dissenso. Pagine recenti della riflessione sulla conoscenza scientifica / Science between consensus and dissent: remarks on scientific knowledge - Giordano, Giuseppe (Rivista Italiana di Filosofia del Linguaggio)
The essay aims to show as if it were distorting an image of science based on a consensus of a research community that necessarily derives from theoretical innovations and discoveries. A survey of twentieth-century epistemology reveals how a standardized vision has been passed, thanks to the “New Philosophy of Science”, and it has been recognized that in the formation of scientific consensus, factors, not only logical, but social, political, religious, rhetorical have come into play. Nowadays it is essential to recognize all of these, and therefore also the dialectic between assent and dissent, because only in this way can science recognize itself “humanist" and not alienating.